Maqāṣidī Hermeneutics: an Istinbāṭ Offer of Islamic Economic Fatwa in the Digital Era - Muhajir; Achmad Nursobah (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Introduction: Islamic economic jurisprudence faces significant challenges in addressing the complexities of the rapidly evolving digital financial systems. This article proposes a novel legal reasoning model called Maqāṣidī Hermeneutics, which synthesizes Fazlur Rahman’s Double Movement method with the objectives of Islamic law (maqāṣid al-sharī‘ah). Methods: The model is constructed through four analytical stages: historical contextualization, maqāṣid identification, legal norm recontextualization, and the formulation of contemporary fatwas. Through case studies of DSN-MUI fatwas on e-money, fintech, and cryptocurrency, the study demonstrates how this approach enables more responsive, relevant, and benefit-oriented rulings. Employing a qualitative method and hermeneutic analysis, the research integrates textual studies with actual fatwa practices. Results: The findings show that the model bridges the classical texts and contemporary contexts while reinforcing ethical and epistemological foundations in Islamic legal reasoning. Conclusion and suggestion: This study aims to offer a theoretical contribution to the development of a more contextual, progressive, and sharia-based methodology for Islamic digital fatwas.